MESSAGE OF THE LEGISLATIVE AND OTHER AUTHORITIES CONCEPTUAL DOCUMENTS AS SOURCES LAWMAKING POLICY - Andrei Petrovich Mazurenko (Современная наука и инновации)
The problem of forms (sources) lawmaking policy. The role and value of the Russian President and heads of Federation subjects messages to legislative (representative) authorities, and also other documents conceptual character, as sources of law-making policy formation at the federal and regional levels are analyzed. The conclusions proving need of conceptualization of the purposes and problems of such policy are drawn. Offered a number of definitions copyrights considered in the paper of scientific concepts.